A luminescent Cd(II)-MOF as recyclable bi-responsive sensor for detecting TNP and iron(III)/silver(I) with high selectivity and sensitivity. (1st October 2018) - Hu, Jinsong; Wu, Ke; Dong, Shengju; Zheng, Mingdong
Graphical abstract: A new Cd(II)-MOFs were synthesized and structurally characterized. Complex 1 is promising bifunctional luminescent probe for highly selective and sensitive sensing TNP and Fe 3+ ions through luminescence quenching effect. The quenching mechanisms were studied based on both experiments and calculation. Abstract: A new three dimensional framework {[Cd2 (BPDPE)2 (chdc)2 (H2 O)2 ]·4H2 O} n (1 ) (BPDPE = 4, 4′-bis(pyridyl)diphenyl ether H2 chdc = 1, 4-cyclohexanedicarboxylic acid) has been successfully synthesized and characterized. In this complex, the chdc 2− adopts tran - configuration, was linked by three types of Cd ions to form wave-like 2D layer with hexagonal grids. The 2D layers are linked by meso-helical chains Cd n (BPDPE) n to form a 3D framework. It is surprised find that complex 1 can highly sensitive sense 2, 4, 6-trinitrophenol (TNP) through luminescence quenching effect, the quenching constant is up to 2.794 × 10 5  M −1 . In addition, complex 1 also presents highly sensitive fluorescent sensor for detecting Fe 3+ and Ag + ions. The quenching constants are 2.893 × 10 4  M −1 and 1.483 × 10 4  M −1 . Furthermore, the quenching mechanisms of complex 1 as multifunctional sensor have been studied.